Amphiphilic oligoamide α-helix peptidomimetics inhibit islet amyloid polypeptide aggregation. Issue 23 (3rd June 2015) - Kulikov, Oleg V.; Kumar, Sunil; Magzoub, Mazin; Knipe, Peter C.; Saraogi, Ishu; Thompson, Sam; Miranker, Andrew D.; Hamilton, Andrew D.
Graphical abstract: Abstract: The abnormal deposition of proteins as insoluble plaques is associated with many diseases, including Alzheimer's, Parkinson's and type II diabetes. There is an unmet need for synthetic agents that are able to mediate particular steps in the pathway between soluble proteins in their native unfolded state and their insoluble β-sheet rich aggregates. We have previously reported classes of α-helix mimetic that agonize or antagonize islet amyloid polypeptide aggregation, depending on the presence of a lipid bilayer. Here we investigate a novel mixed benzamide and pyridylamide scaffold that gives improved activity and explores the role of side-chain polarity, backbone rigidity and curvature in inhibiting lipid-catalyzed fibrillization.